EFEK IMUNOMODULATOR EKSTRAK AIR CINCAU HITAM (Mesona palustris BL) TERHADAP KARSINOGENESIS MENCIT [Immunomodulatory Effects of Water Extracts of Black Cincau (Mesona palustris BL) on Carcinogenesis in Mice] - Tri Dewanti W.; . Sukardiman; Djoko Agus P.; Win Darmanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
Janggelan or black cincau (Mesona palustris BL) is commonly consumed as dessert and also used as herbal remedy in the folk medicine. This study aimed to test the potency of water extract of black cincau in inhibiting fibrosarcoma cancer induced by benzo(a)pyrene. Mice used in this study were divided into 6 groups. Solution of benzo(a)pyrene 0.3% was given during two days for five times to induce cancer. Water extract of black cincau at concentration of 100, 500 and 1000 mg/kg BW was given daily for 2 weeks before initiation (induction of benzo(a)pyrene) during the initiation and until 4 weeks after initiation. The IFN-γ was observed with IFN-y ELISA Kit immunosurveillance parameters while the CD8+, NK cells and macrophages were observed with a flow cytometer. Cancer incidence was observed by palpation every week until 10 weeks after benzo(a)pyrene last induction. The results showed that a high dose of water extract of black cincau (1000 mg/kg BW) increased IFN-γ expression and immunosurveillance of CD8+, NK cells and macrophages of the mice. The treatment also increased cell apoptosis and reduced the cancer incidence in mice by 57%.